Current issues in the management of patients with HIV infection and rheumatic diseases - G. I. Gridneva; B. S. Belov (Современная ревматология, 2021)
According to experts, the human immunodeficiency virus (HIV) epidemic has a steady downward trend, but the attention of the medical community to this problem is not waning. Before the introduction of highly active antiretroviral therapy, the prevalence of rheumatic manifestations in HIV-infected patients ranged from 3 to 71% and was associated with late stages of infection and severe immunosuppression. HIV-associated arthritis, reactive arthritis, psoriatic arthritis, arthralgias and diffuse infiltrative lymphocytosis syndrome are the most common rheumatic pathologies in HIV. Most people with HIV and musculoskeletal inflammatory disease respond well to NSAIDs, opioids, and basic anti-inflammatory drugs. In cases that are torpid to the abovementioned treatment, the use of biologic disease-modifying antirheumatic drugs may be required.The lecture summarizes modern data on the features of the course and treatment of immunoinflammatory rheumatic diseases in HIV infection.